Sistem Pendukung Keputusan PPDB di SMAN Unggul Dharmasraya - Evi Yulia Susanti (Journal of Applied Computer Science and Technology, 2023)
Acceptance of New Students is the initial process in educational institutions to screen prospective students who meet the criteria set by the school. SMAN Unggul Dharmasraya screens prospective students through report cards and written tests. In terms of enthusiasts, this school is classified as a school that has a lot of enthusiasts because it is facilitated by boarding.Therefore, each committee selection process has difficulty in determining prospective students who will be accepted according to the criteria. From these problems the idea emerged to conduct research on the application of decision support systems in accepting new students using the Simple Additive Weighting method. This method is known as the weighted sum method, because the basic concept of SAW is to find the weighted sum of the performance ratings for each alternative on all attributes so that this method can assist in the ranking process based on the results of the assessment of predetermined criteria. The rating of each attribute must be dimension-free in the sense that it has passed the previous matrix normalization process. The purpose of this research was to assist the admissions committee for new students in making decisions to determine prospective new students according to predetermined criteria and weights. The system development model used is the waterfall model, because this model uses a systematic and sequential approach. The results of this study are a decision support system using the Simple Additive Weighting method from calculating the prevalence value, there are several alternatives that can be recommendations for the committee to get prospective students who meet the criteria determined by the school.